Diffuse large B-cell lymphoma and Burkitt lymphoma. Issue 10 (October 2015) - Rodriguez-Justo, Manuel; Marafioti, Teresa
Abstract: Diffuse large B-cell lymphoma is the most commonly diagnosed subtype of lymphoma but represents a heterogeneous group of diseases with specific clinicopathological and immunophenotypical features, molecular pathogenesis and response to treatment. This review focus on DLBCL specific types/subtypes with emphasis in new immunophenotypical markers, genetic profiling studies and borderline categories provisionally recognized by the WHO classification dealing with the overlap between Burkitt lymphoma and DLBCL and Hodgkin lymphoma and DLBCL respectively.